Allogeneic and xenogeneic lymphoid reconstitution in a RAG2−/−IL2RGy/− severe combined immunodeficient pig: A preclinical model for intrauterine hematopoietic transplantation - Sper, Renan B.; Proctor, Jessica; Lascina, Odessa; Guo, Ling; Polkoff, Kathryn; Kaeser, Tobias; Simpson, Sean; Borst, Luke; Gleason, Katherine; Zhang, Xia; Collins, Bruce; Murphy, Yanet; et al. (Frontiers in Veterinary Science, 2022)
Mice with severe combined immunodeficiency are commonly used as hosts of human cells. Size, longevity, and physiology, however, limit the extent to which immunodeficient mice can model human systems. To address these limitations, we generated RAG2-/- IL2RGy/- immunodeficient pigs and demonstrate successful engraftment of SLA mismatched allogeneic D42 fetal liver cells, tagged with pH2B-eGFP, and human CD34+ hematopoietic stem cells after in utero cell transplantation. Following intrauterine injection at day 42-45 of gestation, fetuses were allowed to gestate to term and analyzed postnatally for the presence of pig and human B cells, T cells and NK cells in peripheral blood and other lymphoid tissues. Engraftment of allogeneic hematopoietic cells was detected based on co-expression of pH2B-eGFP and various markers of differentiation. Analysis of spleen revealed robust generation and engraftment of pH2B-eGFP mature B cells (and IgH recombination) and mature T cells (and TCR-β recombination), T helper (CD3+CD4+) and T cytotoxic (CD3+CD8+) cells. The thymus revealed engraftment of pH2B-eGFP double negative precursors (CD4-CD8-) as well as double positive (CD4+, CD8+) precursors and single positive T cells. After intrauterine administration of human CD34+ hematopoietic stem cells, analysis of peripheral blood and lymphoid tissues revealed the presence of human T cells (CD3+CD4+ and CD3+CD8+) but no detectable B cells or NK cells. The frequency of human CD45+ cells in the circulation decreased rapidly and were undetectable within two weeks of age. The frequency of human CD45+ cells in the spleen also decreased rapidly, becoming undetectable at three weeks. In contrast, human CD45+CD3+ T cells comprised >70% of cells in the pig thymus at birth and persisted at the same frequency at three weeks. Most human CD3+ cells in the pig's thymus expressed CD4 or CD8, but few cells were double positive (CD4+ CD8+). In addition, human CD3+ cells in the pig thymus contained human T cell excision circles, suggesting de novo development. Our data shows that the pig thymus provides a microenvironment conducive to engraftment, survival and development of human T cells and provide evidence that the developing T cell compartment can be populated to a significant extent by human cells.